KARDIOCHIRURGIA DOROSŁYCHSerum concentration of selected adipocytokines in patients with coronary artery disease suitable for surgical revascularization: a preliminary study - Rachwalik, Maciej; Diakowska, Dorota; Kustrzycki, Wojciech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Introduction: Adipose tissue produces several bioactive mediators - adipocytokines, that influence insulin resistance, diabetes, body-weight homeostasis and inflammation. There has been no precise clinical data about role of adipocytokines in coronary atherosclerosis. Aim of the study : To estimate serum concentrations of selected adipocytokines in patients with coronary artery disease (CAD) suitable for surgical revascularization. Material and methods : The study included 17 patients with CAD, who were surgically treatment in the Department of Cardiac Surgery and 16 healthy controls. Serum concentrations of leptin, adiponectin, apelin and resistin were measured by immunoenzymatic ELISA tests. Data were compared with demographical, clinical and laboratory parameters of CAD patients. Results : Serum leptin concentration was significantly higher in CAD patients when compared to controls (p < 0.05), and serum adiponectin and apelin concentrations were significantly lower in CAD patients than in healthy subjects (both, p < 0.05). The positive correlation between serum leptin levels and BMI (p < 0.05), and the tendency to negative correlation between serum apelin levels and systolic blood pressure (p = 0.054) in CAD patients were observed. Conclusion: Our results suggest that leptin, adiponectin and apelin may play an important role in pathophysiology of CAD. Correlation studies suggest that apelin level can be related to the systolic blood pressure and pathogenesis of hypertension.